Effects of mercury, organic carbon, and microbial inhibition on methylmercury cycling at the profundal sediment-water interface of a sulfate-rich hypereutrophic reservoir. (1st January 2021) - Fuhrmann, Byran C.; Beutel, Marc W.; O'Day, Peggy A.; Tran, Christian; Funk, Andrew; Brower, Sarah; Pasek, Jeffery; Seelos, Mark
Abstract: Methylmercury (MeHg) produced by anaerobic bacteria in lakes and reservoirs, poses a threat to ecosystem and human health due to its ability to bioaccumulate in aquatic food webs. This study used 48-hr microcosm incubations of profundal sediment and bottom water from a sulfate-rich, hypereutrophic reservoir to assess seasonal patterns of MeHg cycling under various treatments. Treatments included addition of air, Hg(II), organic carbon, and microbial inhibitors. Both aeration and sodium molybdate, a sulfate-reducing bacteria (SRB) inhibitor, generally decreased MeHg concentration in microcosm water, likely by inhibiting SRB activity. The methanogenic inhibitor bromoethanesulfonate increased MeHg concentration 2- to 4- fold, suggesting that methanogens were potent demethylators. Pyruvate increased MeHg concentration under moderately reduced conditions, likely by stimulating SRB, but decreased it under highly reduced conditions, likely by stimulating methanogens. Acetate increased MeHg concentration, likely due to the stimulation of acetotrophic SRB. Results suggest that iron-reducing bacteria (IRB) were not especially prominent methylators and MeHg production at the sediment-water interface is elevated under moderately reduced conditions corresponding with SRB activity. In contrast, it is suppressed under oxic conditions due to low SRB activity, and under highly reduced conditions (<-100 mV) due to enhanced demethylation by methanogens. Graphical abstract: Image 1 Highlights: MeHg production was generally repressed under oxic conditions. Moderately reduced conditions and SRB activity led to an increase in MeHg. Specifically, acetogenic SRB appear to be highly efficient methylators. Highly reduced conditions and methanogenic activity led to a decline in MeHg.